Uso de infusiones al 10% de hierba luisa cymbopogon citratus oreganón plectranthus amboinicus y tilo tilia cordata mill en el control de escherichia coli en pollos broilers - Avila Rivas, Selma Denisse (2015)
This research realized at the Farm Santa Ines, belonging to the Technical University of Machala, using 160 broilers chickens, the same that maintained under the standard rules of production system of ships open. The objective was to verify the possible effects of neutralizing infusions to 10% of (Cymbopogon citratus), (Plectranthus amboinicus) and (Tilia cordata mill) in broilers chickens, challenging them with the bacterium Escherichia coli. The investigation lasted 42 days, we distributed 16 random groups of 10 chickens each, considering 4 treatments (T1 =Control, T2 =Tilo, T3 =Hierba Luisa, T4 =Oreganón) with 4 replications each. Was administered 3ml of infusion to 10% in water for each feeder to the treatment, the data were collected for food consumption and weight weekly; for the samples are collected 3g of feces from each treatment with their respective repetitions, laboratory analysis is conducted with a concentrated repetition and each treatment was select 1g feces, it was watered down and sieve in 10ml of sterile saline water. Hence were dilutions from 10x-2 until the dilution 10x-9 and then to their respective media (MacConkey agar). Samples were taken on day 8, 22, 26 and the inoculation of the bacteria on the same day hours later, and the post inoculation samplings were days 15, 36 and 42. The inoculation was performing directly in the digestive tract; administer 1ml of nutrient broth with a pipette. The results show that there were no significant value statistically, but if there was demonstrated the variability of the use of the infusions in the assimilation food and conversion, therefore we can say that if there was a neutralising effect in T2 (lime) and T4 (Oreganon), associated with the control of the population of Escherichia coli.